PEER-REVIEW OF MONOGRAPH OF V. S. RUSALEYEV, O. V. PRUNTOVA, D. A. LOZOVOY “ACTINOBACILLUS PLEUROPNEUMONIAE IN PIGS”. – VLADIMIR: FGBI “ARRIAH”, 2018. – 134 P.: IL. ISBN 978-5-900026-63-3 - S. Р. Yeremin (Ветеринария сегодня)
.